Non-modifiable Risk Factors and Coronary Angiographic finding - Study in a tertiary rural Centre of Bangladesh (KYAMC Journal, 2013)
DOI: http://dx.doi.org/10.3329/kyamcj.v1i1.13301KYAMC Journal Vol.1(1) July 2010, 21-23